Clinical, Dermoscopic and Histopathological Evaluation of Basal Cell Carcinoma Subtypes: A Retrospective Analysis - Yıldız Gürsel Ürün; Sezin Fiçicioğlu; Mustafa Ürün; Nuray Can (Dermatology Practical & Conceptual, 2023)
Introduction: Dermoscopy aids in identifying histopathological subtypes and the presence of clinically undetectable pigmentation in basal cell carcinoma (BCC).